PERISTILAHAN MOTIF KAIN LUNGGI PADA MASYARAKAT MELAYU DUSUN SEMBERANG KABUPATEN SAMBAS - Muhammad Iqbal; Patriantoro Patriantoro; Amriani Amir (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2019)
AbstractThis research is focused on lunggi cloth motifs in the Sambas Malay community. This study deals with the terminology of lunggi cloth motifs which includes 3 analyzes, namely descriptive analysis analyzed with exposure techniques, lexical meaning is analyzed by lexical meaning description techniques, cultural meaning is analyzed by cultural context techniques, and implementation of lunggi fabric motifs in learning text descriptions in classes VII. The research method used in this research is descriptive with a qualitative form. The data source used was the words and actions of the researcher to get information about the lunggi fabric motif from the informant who knew the ins and outs of the fabric motif that was in Semberang Hamlet, Sambas Regency. Data collection techniques are interviews and with a list of images. The following results found 93 lunggi fabric motifs consisting of 3 groups, namely flora, fauna, and nature and objects. Lunggi flora motif, the form of plants amounting to 56 motifs. Meanwhile, this lunggi fabric motif group is made with 15 animal motifs. There is also a part that is made by the weaver to see nature and objects in his life, amounting to 22 lunggi motifs.                               Keywords: Terminology, Lunggi Fabric Motifs, Semantics.